Using Cooperative Integrated Reading and Composition (CIRC) To Improve Reading Comprehension Achievement - Ira Pertiwi; Annisa Astrid; Winny Agustia Riznanda (Jadila: Journal of Development and Innovation in Language and Literature Education, 2024)
The objectives of this study were to see if there was a significant improvement before and after using the CIRC Method at SMP Nurul Amal Palembang, and if there was a significant difference in reading comprehension between students who were taught using CIRC and those who were not. This study used quantitative research with a quasi-experimental design. The sample of the study was taken from the population at eighth grade consisting of 56 students from two class. The data were obtained from pre-test and post-test. The instrument of the research are pre-test and post-test and the researcher used t-test formula for collecting data. To determine the improvement before and after implementing the CIRC method, a paired sample t-test was conducted. The result indicated that there was significant improvement in students’ reading comprehension achievement through CIRC method with the value of sig. (2-tailed) 000 lower than 0.05. Therefore, the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. It suggests that using CIRC to teach reading enhances students’ reading comprehension. To determine the difference between those who were taught using CIRC and those who were not, an independent sample t-test was conducted, and the results showed that p-output (sig. (2-tailed)) was 0.000 less than 0.05. It indicates that the alternative theory was accepted. Additionally, the study found that using CIRC method to teach reading comprehension to students is very useful. Because of this, using CIRC method can help students’ reading comprehension.